PENELITIAN DAN PENGEMBANGAN MANAJEMEN SUMBER DAYA MANUSIA PADA SMP ISLAM DONOMULYO - Hariono, Jefri; Klau, Herlina Helmy; Isnaeni, Diana (Universitas Pawyatan Daha, 2023)
This research aims to develop a Human Resource Management quality system at Islamic Junior High School Donomulyo. This research and development use the Design Based Research method with the following steps: (1) Problem Identification (2) Identification of Objectives (3) Preparation of Product Design (4) Product Design Test (5) Evaluation of Product Design Test Results (6) Product Communication. The subject used is Donomulyo Islamic Junior High School, data obtained through observation and interviews, and questionnaires. The questionnaire answers use a Likert scale with 5 assessment categories (1) very inappropriate, (2) not feasible, (3) quite feasible, (4) feasible, (5) very feasible. The data analysis technique uses a percentage of the quality system tested by two academic validators and practitioners. The result of this research is a human resource management quality system at Donomulyo Islamic Junior High School with the following specifications: vision, mission, objectives, organisational structure, job description, quality policy and SOP (Standard Operating Procedure). The limitation in this research is that the scope of the research only covers Human Resource Management. For this reason, researchers suggest that future researchers conduct research and development on other substances.